Síntese e cristaloquímica de complexos nos sistemas 1,3- bis(2-fluorofenil)triazeno/Pd(II) e 1,3-bis- (4-metoxicarbonilfenil)triazeno/Ni(II) - Villis, Paulo Cesar Mendes (2003)
Não foi possível inserir o abstract.